(untitled) (Bangladesh Journal of Botany, 2019)
In the present study, along with scape, leaf surface and mesophyll anatomy of four Hyacinthella species, H. nervosa (Bertol.) Chouard, H. hispida (J.Gay) Chouard, H. siirtensis B. Mathew and H. venusta K. Pers. were studied and the features were compared among the species in this research. After the analysis of data, it was seen that the scape anatomy is close to studied species. However, there are differences when the other species examined as seen in the epiderma has papillose protuberances only in H. nervosa. When the leaf mesophyll is observed, it is seen that H. siirtensis and H. venusta are equifacial, H. hispida is unifacial, H. nervosa is dorsiventral. Raphide crystals are seen in some of the mesophyll cells. While leaves are amphistomatic with anomocytic stomata in all taxa, indumentum and epidermal cell bigness of the surfaces show difference among the species.